2021
DOI: 10.1002/hsr2.414
|View full text |Cite
|
Sign up to set email alerts
|

Psychological autopsy study and risk factors for suicide in Muslim countries

Abstract: Background Suicide and risk factors have been poorly studied in the Muslim‐majority countries that hinder the formulation of prevention strategies and affect suicide prevention eventually. Objectives We aimed at identifying and analyzing the psychological autopsy studies assessing the risk factors for suicide conducted in Muslim‐majority countries. Methods We did a search to trace all the available psychological autopsy studies in the Muslim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Considering Islam, Christianity, and Judaism prohibit suicide, it may in turn affect the prevalence of suicide. The scarcity of data and research assessing suicide in Muslim-majority countries further challenges understanding suicide and associated factors in the region ( 4 ). Additionally, studies have shown the potential presence of a relationship between climate change and mental health ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering Islam, Christianity, and Judaism prohibit suicide, it may in turn affect the prevalence of suicide. The scarcity of data and research assessing suicide in Muslim-majority countries further challenges understanding suicide and associated factors in the region ( 4 ). Additionally, studies have shown the potential presence of a relationship between climate change and mental health ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although low- and middle-income countries account for 79% of suicide cases among adolescents, research delving into suicide, associated risk factors, and prevention is often neglected in said countries ( 3 ). Prior studies have highlighted the scarcity of data and research in Muslim-majority countries, which in turn impacts assessment of prevalence, effective intervention planning and education, and prevention ( 4 ). Suicide is defined as the act of taking one's own life intentionally.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, any risk factor with a specific cause–effect association with suicide is difficult to identify [ 3 ]. Although psychiatric disorders have been identified as important risk factors for suicide consistently, the rate varies between Western countries and LMICs as studies from the former report rates around 90% whilst the LMICs show a much lower rate of mental disorders among suicides [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, several intricacies such as criminal status, stigma towards suicide, extreme dearth of research, poor political will (evidenced by low prevention activities), low-quality data, possible under-reporting and LMIC background have made the situation cloudy. One recent review identified that psychological autopsy studies have been conducted only in five Muslim countries (Bangladesh, Indonesia, Iran, Pakistan, and Turkey) of the world [ 9 ]. Studies have identified the association of lower suicide rates in countries with a higher number of Muslim populations [ 13 , 14 ]; however, the role of wider social determinants such as human development index (HDI), income category of the country, political system, and geographical position, have not been studied in the Muslim majority countries.…”
Section: Introductionmentioning
confidence: 99%
“… 2 A family history of suicide, traumatic incidents, psychological stressors such as relationship breakdown, socioeconomic variables, underlying psychiatric diseases including psychoactive substance use, personality traits, loss of social support, previous suicidal attempts, and maladaptive behaviors are all risk factors for suicide. 3 , 4 , 5 According to the World Health Organisation, every year, 700,000 individuals complete suicide, with more than three‐fourths in low‐ and middle‐income countries and many more attempt suicide and self‐harm. 6 Every suicide is a tragedy that impacts the entire family, community, country, and especially the people left behind.…”
Section: Introductionmentioning
confidence: 99%